2022
DOI: 10.3389/fonc.2022.879398
|View full text |Cite
|
Sign up to set email alerts
|

B Cells in Tumor Microenvironment Associated With The Clinical Benefit to Programmed Cell Death Protein-1 Blockade Therapy in Patients With Advanced Esophageal Squamous Cell Carcinoma

Abstract: BackgroundB cells and B cell-related gene signatures in the tumor microenvironment (TME) are associated with the efficacy of anti-programmed cell death-1 (anti-PD-1) therapy in several cancer types, but not known for esophageal squamous cell carcinoma (ESCC).Patients and MethodsPatients with advanced ESCC receiving anti-PD-1/PD-L1-based therapy were retrospectively included. A targeted RNA profiling of 770 immune-related genes from archival ESCC tissues was performed. Differential immune-related pathways and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 31 publications
1
1
0
Order By: Relevance
“…S3B). This trend aligns with a prior study reporting a positive correlation between B cell infiltration and clinical benefit to PD-1 targeted immunotherapy in advanced ESCC 26 and different cancer types. 27 …”
Section: Exploratory Analysissupporting
confidence: 91%
“…S3B). This trend aligns with a prior study reporting a positive correlation between B cell infiltration and clinical benefit to PD-1 targeted immunotherapy in advanced ESCC 26 and different cancer types. 27 …”
Section: Exploratory Analysissupporting
confidence: 91%
“…Lu et al reported that the PD-1/PD-L pathway also contributes to T cell and B cell development and activation [38]. Guo et al found that B cells in the TME were associated with clinical benefits in patients with advanced ESCC receiving anti-PD-1/PD-L1-based therapy [39]. However, a series of clinical trials have shown that the effective rate of immunotherapy is only about 12% to 30% in EC patients [40][41][42][43].…”
Section: Discussionmentioning
confidence: 99%